Unlocking government effectiveness: the interplay of bureaucratic quality, information technology, voice and accountability / Darusalam, Zuraidah Mohd Sanusi and Marijn Janssen - -, Darusalam; Mohd Sanusi, Zuraidah; Janssen, Marijn (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2023)
A high unemployment rate, poor quality service, rampant corruption cases and low economic growth characterise an ineffective government. In contrast, an effective government is a fundamental element of global economic development. The role of bureaucratic quality towards government effectiveness has generated a growing interest in the modern world. Bureaucratic quality evaluates public bureaucracy on transparency of political leaders and the letter of law to strictly agree with the rules. This study examined the role of bureaucratic quality on government effectiveness by examining the intervening effects of information technology and voice and accountability. We collected 25 years of data (1996 -2021) from eight ASEAN countries. Using the Generalised Method of Moments estimator, we estimated a panel data dependence model to overcome heterogeneity and endogeneity issues. The results showed that bureaucratic quality explained government effectiveness through the intervention of information technology and voice and accountability. This study contributes to how bureaucratic quality and the use of information technology can make government work better, but this can only be done fully if there are also ways for people to get involved and be held accountable.